Mecanismos de resistência em genótipos de palma forrageira à infestação por Dactylopius opuntie associados ao perfil metabólico - Bezerra, Janieire Dorlamis Cordeiro (2018)
The Brazilian Northeast is the second most populous region the Brazil and presents, predominantly, semi-arid climate. Livestock farming has been one of the main skills of this region. Due to the rainfall irregularity observed in the Brazilian Semi-arid region, alternatives have been sought to overcome this situation, such as the cultivation of forage plants with xerophytic characteristics such as forage palm. However, in recent years the carmine scale (Dactylopius opuntiae (Cockerell) (Hemiptera: Dactylopiidae)) has turned into a very aggressive pest causing great economic losses in the productive chain. This insect in the act of feeding inoculates toxins that cause the yellowing, the fall of the rackets and, in more severe cases, the death of the plant. Thus, the objective was to characterize the genotypes of cactus pear on the aspects of insect-plant interaction, chemical-bromatological and metabolomics. Four genotypes of cactus pear of the genus Opuntia (IPA-100003, IPA-200008, IPA-200016 and IPA -200149) and three genotypes of the genus Nopalea (IPA-100004, IPA-200021 and IPA -200205) were evaluated. For the nutritional value studies, the experimental design was completely randomized and factorial scheme 7 x 7, corresponding to 7 genotypes and 7 collection periods (0, 15, 30, 45, 60, 75 and 90 days of infestation with Dactylopius opuntiae), with 5 replicates for the insect count and 3 for the laboratory analyzes. For the studies of the metabolites completely randomized experimental design and 7 x 3 factorial scheme, corresponding to 7 genotypes and 3 collection periods (0, 60 and 90 days of infestation with Dactylopius opuntiae), with 3 replicates. For the infestation level, there was an interaction effect (P<0.05) between the infestation days and the studied genotypes, which were deployed. In the chemical-bromatological characteristics, interaction (P<0.05) between genotypes and days after infestation was xx observed in all variables, with differences between genotypes and between days (P <0.05), except for variables B2 (digestible fiber), EE (ethereal extract), PB (crude protein), NDT (total digestible nutrients) and CHOT (total carbohydrates) in some genotypes. There was interaction (P<0.05) between genotypes and days after infestation in all parameters of digestibility and degradability. Significance (P<0.05) was observed in the variable IVDMD (in vitro dry matter digestibility) between the genotypes on all infestation days, as well as for each genotype in relation to the days. For the variable DEG MS (dry matter degradability) it was observed that there was no significant difference (P>0.05) from days 0 to 45 days and in the genotypes IPA-100003, IPA-100004 and IPA-200205. All genotypes of the genus Opuntia reduced total gas production throughout the study. The days of infestation did little to change the nutritional value. Infestation pressure reduced total gas production in all genotypes of the genus Opuntia, mainly in IPA-100003 and IPA-200008, which also showed the largest decreases in CNF production. In the genus Nopalea the infestation pressure influenced the total production of gases in the IPA-200021, mainly between 15 and 60 days of infestation. In the metabolite studies, the formation of five groups was observed. The genus Nopalea was in two groups, only the IPA-100004 at 60 days and the IPA-200021 at 90 years presented a different group from the others. The genus Opuntia was present in all groups. The phytochemical profile of genotypes of the genus Nopalea was not altered by infestation pressure. In the Opuntia genus, it was evident the phytochemical profile change in the insect-plant interaction, mainly in the genotypes IPA-200008 and IPA-100003. The first two major components accounted for 81% of the variations of the original measurements. It was observed that the chemical peaks that most influenced the chemical response of the plant during the attack were 0.84, 0.88, 1.20, 1.24, 1.28, 3.84, 3.88, 4.04, 4.08 ppm, which mainly influenced the genotypes at 60 days after infestation. Therefore, it is necessary to identify the possible compounds in these displacements and which could be related to the responses of the insect-plant interaction. Of the 26 primers used, 24 generated 890 amplified bands, 206 polymorphic loci and 36 monomeric loci. The number of fragments varied from 5 (primer OPG 10) to 12 (primer OPG 06) for RAPD, 8 (primers UBC 842 and UBC 864) at 19 (primers UBC 808 and UBC 827) for ISSR and 4 for ITS, with a mean of 8 for 9 loci per RAPD marker and 11 for 12 xxi loci per marker of ISSR. Genotypes of the genus Nopalea not always group, as well as IPA-100003 and IPA-200008. Our methods of Tocher and major components or genotype IPA-200016 formed a group, highlighting the genus of the genus Opuntia is considered resistant to D. opuntiae. The genotypes IPA-100004 and IPA-200205 in genus Nopalea and IPA-200008 and IPA-200016 in genus Opuntia, have been shown (in this experiment) to be more genetically dissimilar, meaning that they can provide genetic material, linked to the study of promising genotypes based on characters which allows for rapid genetic gains.